The Cabinet of Ministers of Ukraine as a subject of legal relationships of legal responsibility in the pharmaceutical sphere - O. H. Aleksieiev (Zaporozhye State Medical University, 2019)
The aim of work is research of legal status of central executive authorities as subjects of legal relations of legal responsibility arising in the pharmaceutical sphere of Ukraine from the standpoint of pharmaceutical law. Materials and methods. The research material is a modern regulatory and legal framework governing the activities of central executive bodies exercising regulatory influence on the activities of the participants in the pharmaceutical sector of the healthcare industry. During the work, information retrieval, analysis, systematization and generalization methods were used. Results. The Cabinet of Ministers of Ukraine is one of the participants of legal relations in the field of healthcare and the pharmaceutical sector in particular. On the other hand, the CMU is one of the main regulators of such legal relations, and has a significant impact on the general state policy in the field of health care, and on the behavior of individual participants in the pharmaceutical industry. Given this, the issue of the legal responsibility of the government, both a collegial body in general and its individual members in particular, is very important and relevant.